Ilizarov bone transport using an intramedullary cable transportation system in the treatment of tibial bone defects. Issue 6 (June 2021) - Rosteius, Thomas; Pätzholz, Simon; Rausch, Valentin; Lotzien, Sebastian; Behr, Björn; Lehnhardt, Markus; Schildhauer, Thomas Armin; Seybold, Dominik; Geßmann, Jan
Highlights: Bone transport using an intramedullary cable transportation system and Ilizarov ring fixation is a viable treatment option for complex tibial bone defects, which in particular provides advantages in soft tissue healing and axial aligned bone transportation. A standardized, interdisciplinary treatment algorithm is crucial to reach high success rates. Nevertheless, a high number of complications and surgical revisions are associated with this treatment procedure and should be taken into account. Abstract: Introduction: Segmental tibia defects remain challenging for orthopedic surgeons to treat. The aim of this study was to demonstrate bone-related and functional outcomes after treatment of complex tibial bone defects using Ilizarov bone transport with a modified intramedullary cable transportation system (CTS). Patients and Methods: We conducted a single-center, retrospective study including all 42 patients treated for tibial bone loss via Ilizarov bone transport with CTS between 2005 and 2018. Bone-related and functional results were evaluated according to the Association for the Study and Application of Methods of Ilizarov (ASAMI) scoring system. Complication and failure rates were determined by the patients' medical files. Results: Patients had a mean age of 45.5 ± 15.1 years. The mean bone defect size was 7.7 ± 3.4 cm, the average nonunion scoring system (NUSS) score was 59 ± 9.5 points, and the mean follow-up was 40.8 ± 24.4 months (range, 13-139 months). Complete bone and soft tissue healing occurred in 32/42 patients (76.2%). These patients had excellent (10), good (17), fair (2), and poor (3) results based on the ASAMI functional score. Regarding bone stock, 19 patients had excellent, 10 good, and 3 fair results. In total, 37 minor complications and 62 major complications occurred during the study. In 7 patients, bone and soft tissue healing occurred after CTS failure with either an induced membrane technique or classic bone transport; 3 patients underwent lower leg amputation. Patients with treatment failure were significantly older (57.6 vs. 41.8 years; p = 0.003). Charlson score and treatment failure had a positive correlation (Spearman's rho 0.43; p = 0.004). Conclusion: Bone transport using both intramedullary CTS and Ilizarov ring fixation is viable for treating patients with bone loss of the tibia and complex infection or soft tissue conditions. However, a high number of complications and surgical revisions are associated with the treatment of this severe clinical entity and should be taken into account.